2016
DOI: 10.1002/ejp.881
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analytic review of brief guided self‐help education for chronic pain

Abstract: Up to 30% of the population in Western countries suffer from chronic pain. The treatment of chronic pain causes medical and socioeconomic problems. Guided self-help (GSH) might be an effective supplementary treatment, however, the size of this effect is unclear. This meta-analysis quantifies the effect of GSH on chronic pain. A systematic literature search was conducted using PubMed, Cochrane, Psyndex, Psycinfo and Scopus. Studies that investigated GSH in chronic pain conditions (children and adults) were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 106 publications
1
9
0
1
Order By: Relevance
“…While studies on the effect of various self-care therapies for chronic pain are increasing, such as exercise (Chou et al, 2017), tai chi (Chou et al, 2017), yoga (Chou et al, 2017) and mindfulnessbased stress reduction (Cherkin et al, 2016;Chou et al, 2017), the strength of the evidence of effectiveness remains low or moderate (Chou et al, 2007;Rosenquist Richard, 2010;Wong et al, 2017). Even if a recent meta-analytic review 'found small but robust effects of guided self-help interventions for the treatment of chronic pain' (Liegl et al, 2016), more studies about the effectiveness of different types of active self-care are needed, notably to compare the different types of self-care therapies. Self-care methods that showed a higher LOR in this study should be studied first, as they would most likely be accepted by the majority of chronic pain patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies on the effect of various self-care therapies for chronic pain are increasing, such as exercise (Chou et al, 2017), tai chi (Chou et al, 2017), yoga (Chou et al, 2017) and mindfulnessbased stress reduction (Cherkin et al, 2016;Chou et al, 2017), the strength of the evidence of effectiveness remains low or moderate (Chou et al, 2007;Rosenquist Richard, 2010;Wong et al, 2017). Even if a recent meta-analytic review 'found small but robust effects of guided self-help interventions for the treatment of chronic pain' (Liegl et al, 2016), more studies about the effectiveness of different types of active self-care are needed, notably to compare the different types of self-care therapies. Self-care methods that showed a higher LOR in this study should be studied first, as they would most likely be accepted by the majority of chronic pain patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being relatively safe (Crawford et al, 2014b), active self-care 'was associated with decreased pain-related disability, distress, reliance on medication, use of formal health care' and 'better general health' (Blyth et al, 2005). Moreover, a recent metaanalytic review showed a small but robust effect of guided self-help on pain severity and disability in chronic pain patients (Liegl et al, 2016). For example, physical activity adapted to a patient's condition could decrease the prevalence of chronic low back pain (Heneweer et al, 2009), pain intensity and associated disability.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of psychological interventions have been found to be effective in both pain treatment [ 81 84 ] and insomnia treatment [ 73 , 85 ]. Psychological techniques for CP management usually involve strategies for the identification of dysfunctional and/or maladaptive thoughts and specific strategies, such as distraction techniques, relaxation training, and activity pacing.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain is defined as pain experienced every day for at least three months in the previous six [1,4]; it significantly impacts quality of life [5–7] and mental health, with reported associations with depression, anxiety spectrum disorders, and suicidal tendencies [3,8]. Despite the existence of a wide variety of treatments [9], the condition remains one of the most understudied and complex areas of health care systems worldwide [2,10], with a limited number of randomized controlled trials assessing the impact of health professional involvement, education, and singular or combination treatments for all types of chronic pain [1,11–14]. In Australia, waitlists for specialist services are long [1,9,15,16], and access to community services is limited [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…Following all the aforementioned recommendations, the Gold Coast Primary Health Network (GCPHN), an independent organization funded by the Australian government that collaborates with local hospital networks to improve the efficiency and effectiveness of medical services for patients, especially those at risk of poor health outcomes [31], introduced a multidisciplinary chronic pain management program in 2013. The program, called Turning Pain Into Gain (TPIG), is different than others [1,11–14] as it is not restricted to one type of pain, involves multiple health professionals, and adopts as close to a “holistic” approach to patient-centered care as possible via combination of one-on-one clinical service assessments, allied health services, and evidence-based education sessions. Such strategies are all aimed at increasing self-management in participants reporting chronic pain of any etiology and advising their GPs and family members on pain management.…”
Section: Introductionmentioning
confidence: 99%